2019
DOI: 10.1021/acsomega.8b02646
|View full text |Cite
|
Sign up to set email alerts
|

Noble-Metal-Free Iron Nitride/Nitrogen-Doped Graphene Composite for the Oxygen Reduction Reaction

Abstract: Considerable effort has been devoted recently to replace platinum-based catalysts with their non-noble-metal counterparts in the oxygen reduction reaction (ORR) in fuel cells. Nitrogen-doped carbon structures emerged as possible candidates for this role, and their earth-abundant metal-decorated composites showed great promise. Here, we report on the simultaneous formation of nitrogen-doped graphene and iron nitride from the lyophilized mixture of graphene oxide and iron salt by high-temperature annealing in am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 70 publications
2
20
0
Order By: Relevance
“…The result demonstrated a higher ORR activity compared to that of Pt catalyst 67 . Similar results are reported by Varga et al 68 …”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…The result demonstrated a higher ORR activity compared to that of Pt catalyst 67 . Similar results are reported by Varga et al 68 …”
Section: Introductionsupporting
confidence: 89%
“…The result demonstrated a higher ORR activity compared to that of Pt catalyst. 67 Similar results are reported by Varga et al 68 Though the results of the metal carbides and nitrides are promising, their preparation is not an easy task. 69 The reported method for preparing metal nitrides involves the use of corrosive and highly toxic ammonia gas under high temperature.…”
Section: Introductionsupporting
confidence: 75%
“…Additionally, there is an emergence of peak in O 1s XPS at 529.0 eV, which is corresponding to peroxo‐like (O 2 2− ) species, and can be only observed after the OER test. [ 20,34 ] From Raman spectra (Figure S22, Supporting Information), most characterized peaks of metal–nitride disappear, [ 10d,35 ] and three distinct peaks are observed that are corresponding to FeOOH [ 36 ] and CoOOH [ 3a,37 ] This result also confirms the phase transition on the surface of CoVFeN@NF in the OER process. In addition, the surface reconstruction and phase transition of the catalyst were further confirmed by the electrochemical test.…”
Section: Resultsmentioning
confidence: 63%
“…Another major concern for using any catalyst in real-time direct methanol fuel cells is methanol crossover effect which will reduce the ORR catalytic activity and efficacy of the overall system. [74,75] Hence, we compared the methanol crossover effect between the optimized catalyst (Cu(15%)-MFC 60 ) and the wellknown Pt/C using chronoamperometry by introducing methanol into oxygen saturated 0.1 m KOH electrolyte (Figure 10a). Toward this, the normalized current (I/I o ) (current recorded at a given time to that of the initial current) was compared to that of commercial Pt/C.…”
Section: Methanol Tolerance and Stabilitymentioning
confidence: 99%